(untitled) (Polifonia, 2015)
Neste artigo, ancorado na Análise de Discurso pecheutiana e na História das Ideias Linguísticas, a partir de arquivo documental-institucional, analisamos ementários dos componentes curriculares de Língua Portuguesa de um curso de Direito. A análise desses documentos auxilia na compreensão do imaginário de língua e das vertentes de ensino de língua. Investigamos se as vertentes de ensino de língua são autoexcludentes: vários aspectos e questões emergem e compreendemos que os componentes curriculares vão se (re)configurando nas práticas docentes em diálogo com as políticas institucionais para educação, contribuindo para o debate acerca do discurso sobre o ensino de Língua Portuguesa. PALAVRAS-CHAVE: Análise de Discurso, Curso de Direito, Ensino superior de Língua Portuguesa LANGUAGE AND LAW: AN ANALYSIS OF PORTUGUESE LANGUAGE SYLLABUSES IN A LAW UNDERGRADUATE PROGRAM ABSTRACT: In this article, based on Pêcheux’s Discourse Analysis and on the History of Linguistic Ideas, we analyze the table of contents of Portuguese courses in an undergraduate program in Law through an analysis of institutional documents. An analysis of such documents helps to understand the underlying conceptions of language and language teaching. We herein investigate if these conceptions of language teaching are mutually exclusive: many issues arise and we understand that the courses are reconfigured through teaching practices within educational policies. Thereby, we intend to contribute for the debate on discourses about teaching Portuguese. KEYWORDS: Discourse Analysis, Law Program, Teaching Portuguese in Higher Education